Notes for a Substantive Theory of Rural Planning: Evidence from the US Experience. (27th May 2019) - Hibbard, Michael; Frank, Kathryn I
ABSTRACT: Rural areas are the locus of many pressing planning issues, pointing to the need for and possibility of a substantive theory of rural planning. In this article we develop a framework for such a theory. We begin by outlining the emergence of planning and the marginalization of 'the rural, ' by investigating aspects of existing planning theory. Then we explain the framework and apply it to a small set of critical cases in deep rural areas of the U.S. To conclude, we summarize our findings and propose future directions for theory in rural planning.